MSR-FBK IWSLT 2013 SLT System Description - Aue, Anthony; Gao, Qin; Hassan, Hany; He, Xiaodong; Li, Gang; Ruiz, Nicholas; Seide, Frank (International Workshop on Spoken Language Translation (IWSLT), 2013)
This paper describes the systems used for the MSR+FBK submission for the SLT track of IWSLT 2013. Starting from a baseline system we made a series of iterative and additive improvements, including a novel method for processing bilingual data used to train MT systems for use on ASR output. Our primary submission is a system combination of five individual systems, combining the output of multiple ASR engines with multiple MT techniques. There are two contrastive submissions to help place the combined system in xt. We describe the systems used and present results on the test sets.